Penentuan Alih Fungsi Lahan Marginal Menjadi Lahan Pangan Berbasis Algoritma K-Means di Wilayah Kabupaten Boyolali - Kaparang, Daniel; Eko, Sediyono (Universitas Sam Ratulangi, 2013)
Abstract Changes in land use for industrial development, public housing and so on continues to grow along with the increasing of the population. Meanwhile, development of food security, continue to have problems, one of them is wide area of foodland. This study, build an analysis model to supporting variable land suitability against development of marginal land for opening primary food land as an information system. By using K-Means algorithm and focus on the data flow to become information, this study recommends a model of optimization analysis of marginal land to assist Agricultural Department in improving the agricultural service area to plant crops. Key words : Analysis model, K-Means, Marginal Land, Land Food, Characteristic Of The Land Â Abstrak Perubahan fungsi lahan pangan untuk pembangunan industri, perumahan rakyat dan sebagainya, terus berkembang seiring dengan meningkatnya populasi penduduk. Sementara itu pembangunan ketahanan pangan terus mengalami kendala salah satunya luas area lahan pangan. Penelitian ini membangun model analisis variabel pendukung kesesuaian lahan terhadap pengembangan lahan maginal untuk pembukaan lahan pangan sebagai suatu sistem informasi. Dengan menggunakan algoritma k-means dan fokus pada alur data untuk menjadi informasi, maka penelitian ini merekomendasikan model analisis optimasi terhadap lahan marginal untuk membantu dinas pertanian dalam meningkatkan luas area tanam tanaman pangan. Â Kata Kunci: Model analisis, k-means, lahan marginal, lahan pangan, karakteristik lahan